Social innovation in health, community engagement, financing and outcomes: qualitative analysis from the social innovation in health initiative. Issue 3 (10th June 2022) - Moscibrodzki, Patricia; Ahumuza, Emmanuel; Li, Jingjing; Sun, Xiaoming; Tao, Yusha; Van Niekerk, Lindi; Amazigo, Uche; Halpaap, Beatrice; Awor, Phyllis; Tucker, Joseph D
Abstract : Background: Social innovation in health is a community-engaged process that links social change and health improvement, drawing on the diverse strengths of local individuals and institutions. However, there are few studies that examine community engagement, financing and outcomes. The purpose of this study is to use a qualitative descriptive analysis to assess 40 social innovations in health identified through a global open call. Methods: This qualitative analysis examined social innovation case studies from low- and middle-income countries identified by a global social innovation network. A crowdsourcing open call identified projects and key components of each social innovation were evaluated by an independent panel. We used a US Centers for Disease Control and Prevention framework to measure community engagement as shared leadership, collaboration, involvement, consultation or informing. We used descriptive statistics to examine key aspects of community engagement, financing, health outcomes and non-health outcomes. Results: Data from 40 social innovations were examined. Social innovations were from Africa (21/40), Asia (11/40), and Latin America and the Caribbean (8/40). Community engagement was diverse and robust across the cases and 60% (24/40) had either shared leadership or collaboration. Financing for social innovation came from research grants (23), national or provincial government support (15), revenues from sales (13), donations (13) and local government support (10). Social innovations reported health and non-health outcomes. Conclusion: Our data demonstrate social innovations had robust community engagement. Innovative financing mechanisms provide mechanisms for sustaining social innovations. Further research on health and non-health outcomes of social innovation is needed.